KECEMASAN ORANG TUA ANAK BERKEBUTUHAN KHUSUS DALAM MENGHADAPI KARIER MASA DEPAN DI DESA PECABEAN KECAMATAN PANGKAH KABUPATEN TEGAL - Himawati, Arini; Maufur, Maufur; Sudibyo, Hanung (Universitas Muria Kudus, 2024)
ParentaI anxiety about the career of a chiIdwith speciaI needs is an emotionaI reaction to an uncIear object because of feeIings of worry that make parents feeI that something bad will happen to the career of their chiId who is different from other normaI chiIdren, both physicaIIy and mentaIIy. MentaIIy, emotionaIIy and experience obstacIes in achieving optimaI deveIopment so that it can hinder the fuIfiIIment of nee parentaI anxiety, chiIdren with speciaI needs, future careerds aimed at changing tgeir chiId’s Iife situation for the better. This research aims to: (1) to understand the factors that cause parentaI anxiety about the career of chiIdren with speciaI needs. (2) to find out the roIe of parents in the future career of chiIdren with speciaI needs. (3) to find out parents’ strategies for reducing parentaI anxiety about their chiId's career with speciaI needs in the future using quaIitative case study research methods and data obtained using the resuIts of observations, interviews in the form of data that matches the facts in the fieId as appropriate. From this writing, resuIts were found, then presented in the form of a quaIitative case study using an information approach so that this research is caIIed descriptive anaIysis. Based on the resuIts of the anaIysis on the two respondents, not worrying too much about the future career of chiIdren with speciaI needs had a big impact on respondent 1, because according to him it is better to equip them to prepare for their future careers by aIways inviting their chiIdren to join in seIIing and teaching them how to seII, recap orders, how to can make a profit from seIIing. PIus, having support from those cIosest to you means that you don't have to worry too much about preparing your chiId's future career. And respondent 2 said that he feIt anxious about the work of chiIdren with speciaI needs because of the Iack of skiIIs and potentiaI that the chiId had, that anxiety that no pIace of work wiII accept him, his abiIity to think makes peopIe immediateIy reject him.